(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A power transformer is a crucial component in power system networks. Ensuring the optimal operation of power transformers is essential for efficiently supplying energy to utilities. A key part of a power transformer is its insulation system, which includes transformer insulation oil and transformer insulation paper. Indeed, paper insulation is a critical component in transformers due to its role in electrical insulation and thermal performance. Since it’s challenging to test the paper insulation while the transformer is in operation, comprehensive testing before its application is essential. In the paper, comprehensive test methods for evaluating the various parameters of transformer paper insulation are discussed, providing crucial insights for the power industry.